Conflict And Conflict Management In Southeast Asia - Kamarulzaman, Askandar (Penerbit USM, 2000)
Southeast Asia in the year 2001 is a region still beset by domestic conflicts and international tensions. This is despite the long experience the Southeast Asian countries have had in managing conflicts and maintaining inter-state relations, and also despite a period of economic boom in the early to mid 1990s which have resulted in relative peace and stability for the region.